1999
DOI: 10.1111/j.1600-0749.1999.tb00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Sound Needs Sound Melanocytes to Be Heard

Abstract: Intermediate cells in the stria vascularis of the mammalian cochlea are melanocytes, which contain melanin pigments and are capable of synthesizing melanin. These melanocytes are required for normal development of the cochlea, as evidenced by studies of mutant mice with congenital melanocyte anomalies. Melanocytes are also needed for developed cochleae to function normally, as evidenced by studies of mutant mice with late-onset melanocyte anomaly and humans with acquired melanocyte anomaly. Melanin, per se, do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(121 citation statements)
references
References 80 publications
1
118
0
1
Order By: Relevance
“…Melanocytes also populate vestibular regions and the endolymphatic apparatus in the mammalian ear (Masuda et al, 1994;Escobar et al, 1995;Peters et al, 1995;Stanchina et al, 2006), but their role here is less clear; for example, mutations in Kcnj10 have no effect on vestibular endolymph (Marcus et al, 2002). Analysis of the inner ear phenotype in murine models of WS and other auditory-pigmentary disorders has focused on the presence of intermediate cells in the stria vascularis; deafness is usually attributed to the loss of intermediate cells in this tissue, leading to a reduction or collapse of endolymph volume, a loss of the endocochlear potential and subsequent hair cell degeneration (Tachibana et al, 1992;Cable et al, 1994;Matsushima et al, 2002;Stanchina et al, 2006) (reviewed by Tachibana, 1999;Tachibana et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanocytes also populate vestibular regions and the endolymphatic apparatus in the mammalian ear (Masuda et al, 1994;Escobar et al, 1995;Peters et al, 1995;Stanchina et al, 2006), but their role here is less clear; for example, mutations in Kcnj10 have no effect on vestibular endolymph (Marcus et al, 2002). Analysis of the inner ear phenotype in murine models of WS and other auditory-pigmentary disorders has focused on the presence of intermediate cells in the stria vascularis; deafness is usually attributed to the loss of intermediate cells in this tissue, leading to a reduction or collapse of endolymph volume, a loss of the endocochlear potential and subsequent hair cell degeneration (Tachibana et al, 1992;Cable et al, 1994;Matsushima et al, 2002;Stanchina et al, 2006) (reviewed by Tachibana, 1999;Tachibana et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, neural-crest-derived melanocytes populate the stria vascularis of the cochlea as intermediate cells. These are thought to play a protective role and are essential for both the maintenance of endolymph composition and generation of the endocochlear potential (Steel and Barkway, 1989;Cable et al, 1992;Cable et al, 1993;Cable et al, 1994) (reviewed by Steel, 1995;Tachibana, 1999;Price and Fisher, 2001;Wangemann, 2002;Wangemann, 2006;Lang et al, 2007). In the mouse, maintenance of the endocochlear potential depends on expression of the potassium channel Kcnj10 in intermediate cells (Marcus et al, 2002;Wangemann et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing amounts of UV-light, meaning increasing doses of sunlight, causes the melanocytes to increase their production of melanin. Melanocytes also produce pigment for the hair follicles, and they are also present in the cochlea (Tachibana, 1999;Uehara et al, 2009), brain (Goldgeier et al, 1984;, and adipose tissue ) and several other sites 10 . e retinal pigment epithelium of the eyes is also made up of another pigment-producing cell type .…”
Section: Melanocytes and Pigmentationmentioning
confidence: 99%
“…It has been demonstrated that the high throughput of K ϩ across ICs membrane yields EP (14,52,53). A combination of immunohistochemistry (16,54), pharmacological (44), and null mutant mice experiments (17) have resulted in the assertion that Kir4.1 channels residing at membranes of intermediate cells in the StV confer the extrusion of K ϩ to polarize the membrane.…”
Section: Kir41 In the Inner Earmentioning
confidence: 99%